Textual merge based on language-specific syntactic separators - Clementino, Jônatas; Borba, Paulo; Cavalcanti, Guilherme (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
In practice, developers mostly use purely textual, line-based, merge tools. Such tools, however, often report false conflicts. Researchers have then proposed AST-based tools that explore language syntactic structure to reduce false conflicts. Nevertheless, these approaches might negatively impact merge performance, and demand the creation of a new tool for each language. Trying to simulate the behavior of AST-based tools without their drawbacks, this paper proposes and analyzes a purely textual, separator-based, merge tool that aims to simulate AST-based tools by considering programming language syntactic separators, instead of just lines, when comparing and merging changes. The obtained results show that the separator-based textual approach might reduce the number of false conflicts when compared to the line-based approach. The new solution makes room for future studies and hybrid merge tools.